Case Report and Analysis of an Intriguing Phenomenon in Schizophrenia: Incubus Syndrome - Porineeta Gogoi; Soumitra Ghosh (Journal of Psychosexual Health, 2025)
This case report examines Incubus syndrome, blending medieval folklore and psychiatric phenomenology, using a rare case from Northeast India to highlight the limited literature. It focuses on the case of a 45-year-old woman with schizophrenia, post-separation from her spouse, who experienced auditory hallucinations of a benevolent male figure, sensations of being touched, and rhythmic movements of a phallus. The concept has shifted from a folkloric view to that of a recognised psychopathological condition, linked to various disorders like schizophrenia and sleep-related disorders.